Analysis of Additional Employee Income Implementation at The Regional Personnel Agency of Bengkulu Province - Irvan Thamuri; Djonet Santoso; Iqbal Miftakhul Mujtahid (Universitas Medan Area, 2023)
This article aims to analyze and explore the implementation of Additional Employee Income at the Regional Personnel Agency of Bengkulu Province. The problem is focused on the implementation of Additional Employee Income at the Bengkulu Province Regional Personnel Agency with informants consisting of officials, implementers and admin operators of the Bengkulu Province Regional Personnel Agency. In order to approach this problem, the theoretical reference from Erward III is used that the policy implementation factor is needed because there are policy problems that need to be addressed and solved. The data were collected through in-depth interviews, observation and document study, and analyzed descriptively qualitatively. This study concludes that the implementation of Additional Employee Income at the Regional Personnel Agency of Bengkulu Province is seen from 4 aspects, namely from the communication aspect that has gone well but the determination of the additional value of income which is considered insufficient and unfair because it is considered not in accordance with the workload, the Resource Aspect consists of Human Resources are sufficient and meet the criteria and adequate facilities and infrastructure. The Disposition Aspect has been going well, it's just that the amount of additional income needs to be considered based on performance criteria, while from the Bureaucratic Structure Aspect the implementation of additional employee income is in accordance with the existing structure.